Encapsulation of therapeutic protein within polymeric nanofiber using co-axial electrospinning - Mohamad Muhaimin, Zalani (2012)
A drug delivery system is designed to provide a therapeutic agent in the needed amount,at the right time and to the proper location in the body in a manner that optimizes the efficacy,increases compliance and minimizes side effects.In order to study the encapsulation of therapeutic protein within polymeric nanofiber for controlled release using co-axial electrospinning method,a number of main processing parameters were taken into considerations which are formulation of drug loading,polymer and protein concentration and solution flow rate.Polymeric drug delivery device was developed via electrospinning technique using biodegradable Polymer A.Co-axial electrospinning configuration was used to encapsulate various mixtures of Drug 0066,Drug 0360 and also Polymer B as support into the electrospun nanofibers.Using the configuration,two separate solutions flowed through two different capillaries and electrospun through co-axial nozzle configuration setup.The electrified jet will undergo stretching, leading to formation of long and thin thread. When the liquid jet is continuously elongated, the solvent will evaporate.The grounded collector will attract the charged fiber.The morphology of the electrospun nanofibers were analyzed using Field Emission Scanning Electron Microscopy (FE-SEM) and Transmission Electron Microscopy(TEM).The hydrophilicity of electrospun nanofibers were determined using Surface Contact Angle machine.Fourier Transform Infrared Spectrometry(FT-IR)was used to detect the organic group of the electrospun nanofibers.In vitro release studies were conducted to evaluate sustained release potential of the core-sheath structure composite nanofiber.The results showed that the TEM images clearly proved the core/shell structure of nanofibers for the encapsulation of Drug 0066/Drug 0350 within Polymer A.SEM also showed there was an arch appeared within the nanofiber.The present study would provide a basis for further design and optimization of processing conditions to control the nanostructure of core-sheath composite nanofibers and ultimately achieve desired release kinetics of bioactive proteins(e.g., growth factors)for practical tissue engineering applications.